The effectiveness of the studycat application on early childhood english vocabulary mastery in recognizing animals at Kemala Bhayangkari 03 Kindergarten, Alai Padang - Nifa, Hanifah Amran; Elise Muryanti (IKIP Siliwangi, 2024)
Considerable challenges, such as the underutilization of digital media for pre-literacy instruction, have prompted this study. Examining the efficacy of the Studycat app in teaching young children English vocabulary is the primary goal of this study. This study used a quasi-experimental design. In this research, 80 youngsters served as the population. Summarized in Indonesian. Various tests are used to analyze the data, including those for normality, homogeneity, hypothesis testing, and effect size. The comparison between the experimental and control groups' pre- and post-test averages revealed that the former had an average of 11.5 and 9.3, respectively, while the latter had an average of 11 after the experiment. This distinction arises because the Studycat app piques the attention of youngsters more than other learning tools since it allows them to play the app directly. The hypothesis test findings show this to be true since Levene's test of variance yields a significance value (sig) of 0.651 > 0.05. It follows that the control group and the experimental group have similar or identical variances in the N-gain data. Accordingly, it is reasonable to assume that instructors' approaches to teaching English to young students vary significantly from the impact of the Studycat app.